PASAR TENAGA KERJA KABUPATEN BANGKALAN - Andri Wijanarko; Yustina Chrismardani (Trunojoyo University of Madura, 2016)
Kabupaten Bangkalan is a gateway that has been connected Madura island with Surabaya City, the capital city of East Java Province, through Suramadu bridge. This study investigates the pattern of labor demand in Bangkalan. The pattern of labor demand is very important to be known, especially by Division of Social, Manpower and Transmigration Bangkalan, the authorized which provide guidance and address the labor problemsThe method used is technically primary data collection through surveys and interviews to the company (employer) in five main districts, namely District of Bangkalan, District of Socah, District of Kamal, District of Labang and District of Burneh. The purpose of this study to know the pattern of demand for labor in Bangkalan so that The Bangkalan Agency of Social, Manpower and Transmigration can use the results of such research in developing planning strategies more better targeted.Based on the survey, in 2016 is expected to increase the labor demand at high school education level who initially was balanced between primary education and highschool education level of workers. Likewise, in 2017 and 2018 was still dominated by the high school education level of workers, followed by undergraduate level. Recommendations from this study is the need for attention and follow-up of the The Bangkalan Agency of Social, Manpower and Transmigration to be able to open a Training Center more in some locations, especially Training Centre at the district level to train the workforce skills at the level of high school education, and implement the Job Fair in order to facilitate labor undergraduate level to get a job.